Relationship between stress and coronary heart disease. (February 2014) - Kurd, Bushra Jawaid; Dar, Mudassir Iqbal; Shoaib, Maria; Malik, Laraib; Aijaz, Zobia; Asif, Iqra
Background: Coronary heart disease is the leading cause of death worldwide and accounts for 13.7% of deaths in countries like Pakistan. Its association with stress has not been well considered in our setup. Patients with coronary artery disease admitted for coronary artery bypass grafting may have a high prevalence of stress that might increase the risk of adverse outcomes. Methods: 60 patients with coronary artery disease admitted to the Civil Hospital Karachi for coronary artery bypass graft surgery from January 1 to March 31, 2012, were evaluated using a stress evaluation scale. Results: Stress of varying degrees was found to be a significant independent risk factor in patients with coronary heart disease. Analysis of our collected sample of patients with stress showed 60% with high stress ( p = 0.025) and 36.7% moderate stress ( p = 0.0025). An appreciable relationship was found between stress and patient age, sex, body mass index, blood group, and the incidence of myocardial infarction. Conclusion: Our study found evidence of an independent causative association between psychological stress and coronary heart disease, of a similar order to the more conventional coronary heart disease risk factors.